Regional patterns of fortification and single forts : evaluating the articulation of regional sociopolitical dynamics with localized phenomena - Brown Vega, Margaret (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
After more than five decades of research in a number of Peruvian coastal valleys there are abundant survey data available that can be brought to bear on anthropological problems of a regional scale. Given the tools available to us today, such as geographic infarmation systems and powerful computers far carrying out analyses in such spatial databases, studies of regions and even larger areas, are more feasible (Kantner 2008:43-44). Befare such analyses can be carried out, however, such data must be brought together in a manner that makes them amenable to analysis.

Después de más de cinco décadas de investigaciones en varios valles costeros de Perú, existen abundantes datos de reconocimiento que pueden ser utilizados para resolver problemas antropológicos en una escala regional. Dadas las herramientas con las que contamos hoy en día-como los sistemas de información geográfica y las computadoras de alto nivel de procesamiento-para llevar a cabo análisis en estas bases de datos, es más factible llevar a cabo estudios regionales e incluso de áreas mayores (Kantner 2008:43-44). Sin embargo, antes de poder analizar la información, esta debe ser compilada de manera que permita su análisis.
Patrones regionales de fortificaciones y fortalezas individuales : evaluando la articulación de dinámicas sociopolíticas regionales con fenómenos locales
Páginas 169-189
Keywords: Arqueología--Perú--Costa Norte; https://purl.org/pe-repo/ocde/ford#6.01.02